Pengaruh Return On Asset, Current Ratio, Earning Per Share, dan Debt To Equity Ratio Terhadap Harga Saham: Studi Empiris pada Perusahaan Sub Sektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Periode 2020-2024 - Astri Mulyati; Retno Fuji Oktaviani (Jurnal Inovasi Manajemen, Kewirausahaan, Bisnis dan Digital, 2025)
This study aims to analyze and determine the effect of Return on Assets (ROA), Current Ratio (CR), Earnings Per Share (EPS), and Debt to Equity Ratio (DER) on company stock prices. The focus of the study was directed at food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. This sub-sector was chosen because it has a strategic role in the Indonesian economy, as well as being one of the sectors that is relatively stable and has long-term growth prospects. This study uses secondary data in the form of annual financial reports and stock price information obtained from the official IDX website. The sampling method was carried out using a purposive sampling technique, namely selecting samples based on certain criteria. From a total population of 94 companies, 19 companies were obtained that met the criteria as research samples. The data were then analyzed using multiple linear regression analysis methods with the help of Statistical Program for Social Science (SPSS) software version 22. The results of the study indicate that ROA has a significant effect on stock prices, which means that the higher the company's ability to generate profits from its assets, the greater investor confidence is reflected in the increase in stock prices. The CR variable also proved to influence stock prices, indicating that a company's liquidity is a consideration for investors in investment decisions. Conversely, the EPS variable did not significantly influence stock prices. This suggests that although EPS reflects earnings per share, this information is not always a dominant factor for investors in assessing stock prices in the food and beverage sub-sector. Similarly, the DER variable also had no significant effect, indicating that a company's capital structure does not directly influence market perception of stock prices.